2017
DOI: 10.20990/kilisiibfakademik.316770
|View full text |Cite
|
Sign up to set email alerts
|

Fama Ve French Üç Faktörlü Modeli̇’ni̇n Geçerli̇li̇ği̇ni̇n Borsa İstanbul İçi̇n Panel Veri̇ Anali̇zi̇ İle Araştirilmasi

Abstract: ÖzBu çalışmanın amacı Fama ve French üç faktörlü varlık fiyatlama modelinin Borsa İstanbul'da pay senetleri işlem gören finansal olmayan firmalar için geçerliliğinin test edilmesidir. Bu kapsamda, defter değeri/piyasa değeri oranı, firma büyüklüğü ve pazar portföy getirisi değişkenleri ile pay senedi getirileri arasındaki ilişki panel veri analizi ile incelenmiştir. Araştırma bulgularına göre, firma büyüklüğü ve pay senedi getirileri arasında negatif yönlü; defter değeri/piyasa değeri oranı ile pay senedi geti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…When the studies conducted in Turkey are considered, the validity of the FF3F model in Borsa İstanbul has been tested frequently. In general, the findings confirm the validity of this model in Borsa İstanbul (Atakan & Gökbulut, 2010;Coşkun & Çınar, 2014;Kara, 2016;Kaya & Güngör, 2017). Only, the study of Genç and Çömlekçi (2018: 271) which covers companies included in the Borsa Istanbul corporate governance index between 2010 and 2017, found that small-scale companies performed lower than large-scale companies, unlike FF3F main assumptions.…”
Section: Research Model 321 Model Selectionsupporting
confidence: 66%
“…When the studies conducted in Turkey are considered, the validity of the FF3F model in Borsa İstanbul has been tested frequently. In general, the findings confirm the validity of this model in Borsa İstanbul (Atakan & Gökbulut, 2010;Coşkun & Çınar, 2014;Kara, 2016;Kaya & Güngör, 2017). Only, the study of Genç and Çömlekçi (2018: 271) which covers companies included in the Borsa Istanbul corporate governance index between 2010 and 2017, found that small-scale companies performed lower than large-scale companies, unlike FF3F main assumptions.…”
Section: Research Model 321 Model Selectionsupporting
confidence: 66%